The Theory of Planned Behavior, Past Behavior, Situational Factors, and Self-Identity Factors Drive Indonesian Enterpreneurs to Be Indebtedness - Shine Pintor S. Patiro; Hety Budiyanti (Universitas Pelita Harapan, 2016)
This study investigates the factors affecting borrowing intention among young entrepreneur of Indonesia TDA community based on the Theory of Planned Behavior (TPB). About 100 questionnaires were accepted and analyzed using structural equation modeling (SEM) in determining the relationships. The results show that borrowing intention amongst young entrepreneur of Indonesia TDA community is influenced by attitude, subjective norms, perceived behavior control, self identity, situational temptation, and past behavior. The young entrepreneur of Indonesia TDA community believe that they have complete control of their behavior in borrowing as they perceived to be equipped with the knowledge about the personal financing. In addition, because of their experience in students’ loans since undergraduates’ level, the result explains why situational temptation were found to be a significant predictor. The findings offer implications for researchers and government.